Factores climáticos y su influencia en la expresión de enfermedades fúngicas en cultivares de Heliconias - López-Vásquez, Juan Manuel (2013)
One of the factors limiting the production of heliconias in Colombia is fungal disease, which is influenced by climatic conditions that determine the development of the disease cycle. In order to define a possible relationship between climatic factors and the incidence or severity of the most limiting fungal, we developed a linear correlation analysis of 10 heliconia cultivars in two municipalities, in the departments of Risaralda and Valle del Cauca. We found a direct relationship between the weekly average temperature and the incidence index of Colletotrichum spp., and the severity index of Helminthosporium spp.; areas with weekly average temperatures over 25°C will likely have incidence and severity of these limiting disease exceeding 50 % and 25 % respectively. Based on these results, we propose the development and validation of a predictive model of incidence and severity of limiting diseases, using a climate forecasting system.